THE CONTRIBUTION OF OPERATIONAL EFFICIENCY AND CUSTOMER INTERACTION TO THE POSITIVE IMAGE OF DELIVERY SERVICE USERS - Cantika Sylvia Bayu Hernanda; Mashudi (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study analyzes the effect of service quality and delivery timeliness on customer satisfaction at a regional main branch office of a state-owned logistics service provider. It aims to identify which factors most significantly affect customer satisfaction levels in the logistics delivery sector. Methods: A quantitative explanatory approach was used through survey methodology. Data were collected from 60 customers of the logistics company’s main branch using a structured online questionnaire. The results were processed and analyzed using SPSS Version 25 to evaluate the partial and simultaneous impact of service quality and delivery timeliness on customer satisfaction. Results: The findings indicate that service quality has a positive and significant effect on customer satisfaction, while delivery timeliness does not show a significant partial influence. However, when tested simultaneously, both variables significantly affect satisfaction, with the model explaining 16.5% of the variance in customer satisfaction, leaving 83.5% influenced by other external factors. Novelty: This research offers valuable insights into customer satisfaction dynamics in state-owned postal and logistics services. Emphasizing the dominant role of service quality, it provides strategic recommendations to enhance service standards and strengthen customer trust. The study contributes to improving service competitiveness amid evolving consumer expectations in the logistics sector.